Factors Associated with the Change in Carotid Maximum Intima-Media Thickness in Patients with Moderate-to-Advanced Stage Chronic Kidney Disease - Hirai K (Dove Medical Press, 2020)
Keiji Hirai, Junki Morino, Saori Minato, Shohei Kaneko, Katsunori Yanai, Yuko Mutsuyoshi, Hiroki Ishii, Momoko Matsuyama, Taisuke Kitano, Akinori Aomatsu, Haruhisa Miyazawa, Kiyonori Ito, Yuichiro Ueda, Susumu Ookawara, Yoshiyuki Morishita Division of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, Saitama, JapanCorrespondence: Keiji HiraiDivision of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, 1-847 Amanuma-cho, Omiya-ku, Saitama-shi, Saitama-ken 330-8503, JapanTel +81-48-647-2111Fax +81-48-647-6831Email keijihirai@kfy.biglobe.ne.jpPurpose: The objective of this study was to determine factors associated with the change in carotid maximum intima-media thickness (IMT), an established surrogate marker of atherosclerosis, in moderate-to-advanced stage chronic kidney disease (CKD) patients.Methods: In total, 130 moderate-to-advanced stage CKD patients (mean age: 67.6 ± 11.0 years old; 91 men and 39 women) were included in this retrospective, single-center, observational study. Relationships between the change in carotid maximum IMT and clinical and laboratory data were analyzed by using multivariate linear regression analyses.Results: Mean observation period was 2.9 ± 1.6 years. Mean carotid maximum IMT at baseline was 2.2 ± 1.0 mm, and the annual change in carotid maximum IMT was 0.06 ± 0.22 mm/year. Low-density lipoprotein (LDL)-cholesterol (β = 0.173, p < 0.05) and annual change in triglyceride (β = 0.175, p < 0.05) independently correlated with the annual change in carotid maximum IMT.Conclusion: Increases in LDL-cholesterol and triglyceride were associated with the rate of progression of carotid maximum IMT in moderate-to-advanced stage CKD patients.Keywords: atherosclerosis, carotid maximum intima-media thickness, chronic kidney disease